2011
DOI: 10.1159/000331791
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Adult Extra-Articular Distal Humeral Diaphyseal Fractures Using an Oblique Metaphyseal Locking Compression Plate via a Posterior Approach

Abstract: Objective: The purpose of this study was to evaluate the feasibility and clinical outcome of using an oblique AO (Association for the Study of Internal Fixation) metaphyseal locking compression plate (MLCP) in the treatment of adult extra-articular distal humeral diaphyseal fractures via a posterior approach. Subjects and Methods: A series of 19 cases of adult extra-articular distal humeral diaphyseal fractures were surgically treated using an MLCP and lag screws, if necessary, via a posterior approach. All pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…20 There are numerous other studies which document the efficiency of this plate in treatment of distal humerus fractures. 17,22 The limitations of our study are small sample size and lack of a control group to compare the results. Large randomized controlled trials may be more effective to shed more light on the subject.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…20 There are numerous other studies which document the efficiency of this plate in treatment of distal humerus fractures. 17,22 The limitations of our study are small sample size and lack of a control group to compare the results. Large randomized controlled trials may be more effective to shed more light on the subject.…”
Section: Discussionmentioning
confidence: 93%
“…15 Dual locking plates (orthogonal and parallel) have also been described, but require extensive periosteal stripping for exposure and hence not recommended routinely as this increases chances of non union and infection. 16,17 Other plate designs like the Lambda plate and metaphyseal locking plate have also been described, but none of them are as efficient as the EADHP in terms of biomechanical stability and lesser complications. [18][19][20] In our study, 30 patients were males indicating the higher incidence of distal humerus fractures in males than in females.…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of the soft tissue envelope is an important aspect in fracture healing, and it has led to the change in the earlier concept of anatomic reduction and rigid fixation [17]. This concept is no longer valid for most of the extra-articular fractures with complex fracture patterns, where minimal soft tissue dissection and stable fixation has shown to have better results and is now the standard principle [18]. Although there have been no comparative studies of dual column vs. single column fixation for distal humerus fractures, we believe and suggest that the higher infection and non-union rates quoted in many series of distal humerus fractures may in part be due to greater soft tissue dissection and a longer operative time required for dual column plating [5, 8].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [18] also suggested that the excessive soft tissue dissection required for dual plating may be responsible for the increased incidence of iatrogenic radial nerve palsy reported in some series. Placement of implant over the distal medial aspect of humerus which has a scant soft tissue cover also leads to a high incidence of implant-related complications such as ulnar neuropathy [19].…”
Section: Discussionmentioning
confidence: 99%
“…X-ray films were assessed by an independent reviewer, using the following parameters: [17][18][19] 1. Callus formation on three out of four cortices on anteroposterior and lateral radiographs taken 12 weeks post-operatively…”
Section: Post-operative Carementioning
confidence: 99%